PENGEMBANGAN MEDIA KARTU BERGAMBAR UNTUK MENINGKATKAN PENGETAHUAN PROFESI BAGI ANAK-ANAK SD KELAS ATAS - Setyadi, Dendy (Perspektif Ilmu Pendidikan, 2019)
The purpose of this research is to develop a set of picture products that can be used for students in particular as the introduction of occupations in Indonesia. ‘Research and Development’ method by Borg and Gall was used in this study. This research is categorized into small scale “R&D” since it only used multiple stages, which were: research and information collecting, planning, developing of initial product format, initial product validating, and product revising. The result shows from each validator that media experts assess 90,28% (very decent), material experts assess 78,09% (decent), and students as users assess 78,52% (very decent). From these validations, it can be concluded that picture cards media can be categorized as worthy with the average percentage of 78,52%. These picture cards media are expected to be tested further to be used effectively, furthermore this research is expected to be implemented in other schools.